2021
DOI: 10.1038/s41398-021-01739-3
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality: a powerful technology to provide novel insight into treatment mechanisms of addiction

Abstract: Due to its high ecological validity, virtual reality (VR) technology has emerged as a powerful tool for mental health research. Despite the wide use of VR simulations in research on mental illnesses, the study of addictive processes through the use of VR environments is still at its dawn. In a systematic literature search, we identified 38 reports of research projects using highly immersive head-mounted displays, goggles, or CAVE technologies to provide insight into treatment mechanisms of addictive behaviors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…This approach has been done before using MRI and EEG. In these studies, it was found that VR induced more cravings than other stimulation types (97,98). Natural cues are included as important controls to identify drugspecific cue responses (99).…”
Section: Stimulation Cuesmentioning
confidence: 99%
“…This approach has been done before using MRI and EEG. In these studies, it was found that VR induced more cravings than other stimulation types (97,98). Natural cues are included as important controls to identify drugspecific cue responses (99).…”
Section: Stimulation Cuesmentioning
confidence: 99%
“…Besides, VR technology has emerged as a powerful tool for the research and intervention of addiction [98]. It's a tool to study how proximal multi-sensorial cues, contextual environmental cues, as well as their interaction (complex cues), modulate addictive behaviors.…”
Section: Novel Treatmentsmentioning
confidence: 99%
“…On the other hand, VR allows strict control and wider adaptation of exposure environments to individual needs, such as combining specific drug-related contextual cues (e.g. handling syringes in presence of peers self-injecting cocaine), which could not be used in vivo for safety purposes ( Mazza et al, 2021 ). This might be of particular interest for generalizing CET effects and preventing cue-induced craving rebound (e.g.…”
Section: Introductionmentioning
confidence: 99%